Neuroprotective effect of ischemic preconditioning via modulating the expression of cerebral miRNAs against transient cerebral ischemia in diabetic rats. (1st November 2016) - Altintas, Ozge; Ozgen Altintas, Mehmet; Kumas, Meltem; Asil, Talip
Abstract : Objectives: In this study, we aimed to evaluate the effect of the Ischemic preconditioning (IPreC) on the expression profile of cerebral miRNAs against stroke by induced transient middle cerebral artery occlusion (MCAo) in diabetic rats. Methods: Eighty male Spraque Dawley rats were allocated to eight groups. In order to evaluate the expression profile of miRNAs, we induced transient MCAo seven days after STZ-induced diabetes (DM). Also we performed IPreC 72 h before transient MCAo to assess whether IPreC could have a neuroprotective effect against ischemia-reperfusion injury. Results: The general characteristics of STZ-treated rats included reduced body weight and elevated blood glucose levels compared to non-diabetic ones. We demonstrated that miRNA expression profiles, which are determined for biological functions such as aquaporin 4 formation (miR-29b-2, miR-124a-3p, miR-130a, miR-223 and miR-320a), glutamate toxicity (miR107, miR-145, miR-223), salvageable ischemic area (miR-9a, miR-19b, miR-29b-2, miR-341, miR-339–5p, miR-15–5p, miR-99b-5p), and neoangiogenesis (let-7f-5p, miR-126a and miR-322–3p), were regulated following IPreC. Ischemic preconditioning before cerebral ischemia significantly reduced infarction size compared with the other groups [IPreC + MCAo (27 ± 11 mm 3 ) vs. MCAo (109 ± 15 mm 3 ) p < 0.001; DM + IPreC + MCAo (38 ± 9 mm 3 ) vs. DM + MCAo (165 ± 41 mm 3 ) p < 0.001, respectively]. Discussion: The study results revealed the neuroprotective effects of ischemic preconditioning, supported with the upregulated pro-survival miRNAs in MCA infarcts.